Thermal effects on femtosecond laser pulses on materials - Tran, Duc Vi (2014)
Laser-materials interaction with femtosecond (ultrashort) pulses is different from that of nanosecond (long) pulses, creating significant scientific interest and practical applications. For nanosecond lasers, a significant amount of the laser power irradiated onto a material is conducted away, as evident by the observed molten layers and heat affected zone in the vicinity of the irradiated area. In contrast, irradiation by femtosecond lasers causes hardly any molten materials and limited heat-affected zone. Thus, the current wisdom is that there is negligible, if any, heat conduction for femtosecond laser processing. The existing explanation is that laser pulses of less than a picosecond duration have insufficient time for significant heat conduction to the surrounding area. Hitherto, there has been no direct experimental observation substantiating this explanation. Employing an infrared thermography technique, the temperature field is directly observed in specimens irradiated by femtosecond laser pulses over a large range of laser powers on two different materials, namely crystalline silicon and steel. This experimental set-up is simple, but has a high degree of confidence and repeatability. The results obtained demonstrate that the current belief of no or negligible heat conduction for femtosecond laser processing is unfounded, and that two thirds or more of the laser power are dissipated by the specimens through conduction and heat losses along the specimens, with thermal conduction as the dominant mechanism. These findings have significant implications on the fundamental assumptions of heat conduction and processing with femtosecond laser pulses.